Implementasi Kurikulum Merdeka dalam Pembelajaran Bahasa Arab: Peluang dan Tantangan - Nuzuli, Zikrullah (LaKaspia, 2025)
The Merdeka Curriculum launched by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia aims to provide flexibility for educators and students in the learning process. This study aims to examine the implementation of the Merdeka Curriculum in Arabic language learning, Recognizing and maximizing available opportunities, and challenges faced by teachers in its implementation. This study employs a qualitative approach using literature review and interviews with Arabic language teachers at several madrasahs. The findings indicate that the Merdeka Curriculum offers creative space for designing project-based and contextual learning, but also presents challenges such as limited teaching modules, insufficient teacher training, and low student motivation toward Arabic language learning